2010
DOI: 10.1017/s1368980010002570
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic circumstances and food habits in Eastern, Central and Western European populations

Abstract: Objective To assess the relationship between several socio-economic indicators and frequency of consumption of seven predefined healthy foods (consumption of fruit, vegetables, wholegrain bread, vegetable-fat spread, vegetable cooking fat, low-fat milk and low-fat cheese) in populations from Eastern, Central and Western Europe. Design Analysis of baseline data collected in two cross-sectional cohort studies between 2000 and 2005: the Health, Alcohol and Psychosocial factors In Eastern Europe (HAPIEE) study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 47 publications
5
69
0
9
Order By: Relevance
“…Although numerous studies on the association between SEP and the intake of different groups of AF have been conducted, few of them have examined the independent effect of socio-economic indicators (13,(18)(19)(20)(21)(22) . They showed that findings were not systematically concordant with those of studies using a single SEP. For instance, when adjusted for occupation or income, education was not associated, or was inversely associated, with cheese intake (20,22) , while a large majority of studies using only one SEP indicator showed higher cheese intake among individuals with higher socio-economic status.…”
mentioning
confidence: 99%
“…Although numerous studies on the association between SEP and the intake of different groups of AF have been conducted, few of them have examined the independent effect of socio-economic indicators (13,(18)(19)(20)(21)(22) . They showed that findings were not systematically concordant with those of studies using a single SEP. For instance, when adjusted for occupation or income, education was not associated, or was inversely associated, with cheese intake (20,22) , while a large majority of studies using only one SEP indicator showed higher cheese intake among individuals with higher socio-economic status.…”
mentioning
confidence: 99%
“…Available data that stem from methodologically comparable nutritional surveillances have studied intake and/or status of a few micronutrients within limited life stages, whereas literature reviews have predominantly focused on the relationship between SES and intakes of macronutrients or specific food groups and food patterns (e.g. fat, fruits and vegetables) (1,(5)(6)(7)(8)(9)(10)(11)(12) . Furthermore, the studies have been performed primarily in adults, while children and the elderly might be more vulnerable to insufficiencies.…”
mentioning
confidence: 99%
“…At the same time, they also connect with other unfavourable healthrelated behaviour factors (3,(9)(10). Unhealthy eating and activity habits, which are seen in the nutrition status as overweight and obesity, are seen to a greater extent in women with a lower educational attainment (8,9,24) and over 40% of obesity in women can be attributed to differences in socioeconomic status (24). Even though education has been proven to be a factor of differences, our data indicates that in some cases it is not the key factor.…”
Section: Discussionmentioning
confidence: 99%
“…The sample is not weighed by education. The chosen independent variables are: education, age, community type, region of residence, the presence of a partner and children and self-perceived social class (8)(9)(10). The dependent variables were typical health-related behaviours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation